A Review of Adult, Continuing Education and Extension: Exploring the Impact of Adult, Continuing, and Extension Education (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Latin prefix ex means out, and tension means stretching, therefore extension isa compound word. Extending oneself literally means to spread out. The year 1914 marks the beginningof widespread usage of this word in the United States. When first used, the term referred to a satellitecampus of a larger institution that served students who otherwise would not have been able to attend.That is to say, when people refer to extension education, they are referring to a kind of education thattakes place outside of traditional classroom settings. Extension relies heavily on education. The primaryidea of extension is that it goes beyond conventional schooling. In other words, people grow in wisdomand skill, and acquire the ability to adapt to new circumstances. This refers to the sort of education thatis made available to those living in more remote areas. This goes beyond what can be taught in aclassroom. In this paper Discuss the Adult, Continuing Education and Extension.